Genetics and biotechnology of the H2-uptake [NiFe] hydrogenase from Rhizobium leguminosarum bv. viciae, a legume endosymbiotic bacterium. (1st February 2005) - Palacios, J.M.; Manyani, H.; Martínez, M.; Ureta, A.C.; Brito, B.; Báscones, E.; Rey, L.; Imperial, J.; Ruiz-Argüeso, T.
Abstract : A limited number of strains belonging to several genera of Rhizobiaceae are capable of expressing a hydrogenase system that allows partial or full recycling of hydrogen evolved by nitrogenase, thus increasing the energy efficiency of the nitrogen fixation process. This review is focused on the genetics and biotechnology of the hydrogenase system from Rhizobium leguminosarum bv. viciae, a frequent inhabitant of European soils capable of establishing symbiotic association with peas, lentils, vetches and other legumes.